1971
DOI: 10.1063/1.1675131
|View full text |Cite
|
Sign up to set email alerts
|

Exact Finite Method of Lattice Statistics. V. The Thermodynamic Phases of a Triangular Lattice Gas

Abstract: We present phase diagrams showing the stable phases of a two-dimensional lattice gas. The molecules reside on the triangular lattice and have hard cores which exclude other molecules from the first-and second-neighbor positions. An interaction w (positive or negative) is postulated for molecules separated by the third-neighbor distance, and no interaction is experienced at still greater separation. For attractive third-neighbor interactions (negative 10) the phase diagram possesses only two regions: solid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Next, we study the triangular lattice N2 model (exclusion up to the next-nearest-neighbor). This model was long ago investigated, and early studies suggested that the phase transition is first order [25,26,27]. However, later transfer matrix analysis [28], and recent exhaustive MC results [29] concluded that the model undergoes a second order phase transition at µ c = 1.75682(2) and critical density ρ c = 0.180(4), and is believed to be part of the q = 4 Potts universality class, with σ ′ = 1/3.…”
Section: B Triangular Lattice N2 Modelmentioning
confidence: 99%
“…Next, we study the triangular lattice N2 model (exclusion up to the next-nearest-neighbor). This model was long ago investigated, and early studies suggested that the phase transition is first order [25,26,27]. However, later transfer matrix analysis [28], and recent exhaustive MC results [29] concluded that the model undergoes a second order phase transition at µ c = 1.75682(2) and critical density ρ c = 0.180(4), and is believed to be part of the q = 4 Potts universality class, with σ ′ = 1/3.…”
Section: B Triangular Lattice N2 Modelmentioning
confidence: 99%
“…The LG34 model resembles the phase behavior of the purely repulsive lattice-gas model studied in [16], hereby called LG3, where particles exclude first-and second-neighbor sites on a triangular lattice while softly repelling each other at third-neighbor distance. Both models share the same phases, although LG34 is more effective in promoting the stability of the solids at the expense of the fluid.…”
Section: A Lg34 Modelmentioning
confidence: 99%
“…Thus, one would expect that, if it is second order, the melting of ordered phase should be in the 4-state Potts universality class. However, several studies at the end of 60s last century suggested that the phase transition is first order [8,9]. Later, Bartelt and Einstein [10] reexamined this model by a phenomenological renormalization-transfer-matrix scaling.…”
Section: Introductionmentioning
confidence: 99%